2020
DOI: 10.2147/prbm.s287143
|View full text |Cite
|
Sign up to set email alerts
|

REAC Neuromodulation Treatments in Depression, Anxiety and Stress. A Comparative Retrospective Study

Abstract: Introduction The purpose of this retrospective study was to compare the effects of two different modalities of administration of the neuro psycho physical optimization (NPPO) neuromodulation treatment, applied with radio electric asymmetric conveyer (REAC) biotechnology devices. Both the modalities are aimed at improving the strategies to deal with and optimize the allostatic response to environmental stressors and exposome. This allows to reduce the dysfunctional adaptive behavior patterns, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…REAC technology has been successfully applied in various medical fields, including pain management [ 26 , 68 , 69 ], depression, anxiety, and stress-related disorders [ 34 , 36 , 37 , 70 , 71 , 72 ], neurological disorders [ 35 , 73 , 74 , 75 , 76 ], orthopedics [ 77 , 78 , 79 , 80 ], wound healing [ 30 , 81 , 82 , 83 ] anti senescence [ 84 , 85 , 86 ] and regenerative medicine [ 31 , 32 , 79 , 87 , 88 , 89 ]. Clinical trials have demonstrated the safety and tolerability of REAC technology, with no significant adverse effects reported.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…REAC technology has been successfully applied in various medical fields, including pain management [ 26 , 68 , 69 ], depression, anxiety, and stress-related disorders [ 34 , 36 , 37 , 70 , 71 , 72 ], neurological disorders [ 35 , 73 , 74 , 75 , 76 ], orthopedics [ 77 , 78 , 79 , 80 ], wound healing [ 30 , 81 , 82 , 83 ] anti senescence [ 84 , 85 , 86 ] and regenerative medicine [ 31 , 32 , 79 , 87 , 88 , 89 ]. Clinical trials have demonstrated the safety and tolerability of REAC technology, with no significant adverse effects reported.…”
Section: Methodsmentioning
confidence: 99%
“…Neuro Psycho Physical optimization (NPPO) is a non-invasive, neurobiological modulation treatment. NPPO has been shown to be effective in addressing a range of conditions and symptoms, including chronic pain, anxiety, depression, insomnia, fatigue [ 34 , 36 , 71 , 72 , 92 , 93 , 94 ], and cognitive impairment [ 33 , 74 , 95 ]. These benefits are achieved through the REAC functional optimization of the neurotransmission processes governed by endogenous bioelectrical activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation